Variation in transcriptional profiles of carotenoid biosynthetic genes in Indonesian yellow- and white-fleshed tuberous root cassava (Manihot esculenta Crantz) accessions. Issue 1 (February 2020) - Wahyuni, Y; Anika, M; Putri, D H; Hartati, N S; Harmoko, R; Sudarmonowati, E
Abstract: Root-tubers of cassava ( Manihot esculenta Crantz) accumulate high starchy carbohydrates, protein, and carotenoids. Carotenoids were associated with tuber colorus, i.e., yellow-fleshed tuber accumulates more carotenoids than white-fleshed root-tubers. Carotenoids serve nutrition for health, such as an antioxidant and provitamin A. This study aimed to analyze relative expressions (RE) of carotenoid genes in Indonesian yellow and white cassava (IYC and IWC, respectively). Nine-month-old fresh root-tubers of IYC (Adira-1, Mentega-2, and Ubi Kuning) and IWC (Adira-4 and Menti) were used for the analysis. RE of five genes: PSY (phytoene synthase), CRTISO (carotenoid isomerase), LYCa (α-lycopene cyclase), LYCb (β-lycopene cyclase), and BCH1 (beta carotene hydroxylase1), and a reference gene, i.e., EF1-A ( elongation factor 1-alpha ), were analyzed using a qRT-PCR. Results showed that RE of all genes were detected in IYC and IWC. In IWC, all genes were expressed high, suggesting biosynthetic fluxes through yellow α-carotenoids and xanthophylls. In YWC, variations on RE levels of all genes were observed. LYCa and LYCb were expressed high in Adira-1 and Mentega-2, indicating α- and β-carotenoids accumulate in root-tubers. However, BCH1 was expressed 2-3-folds lower in both accessions than all IWC, suggesting low zeaxanthin production and accumulation of β-carotene. In Ubi Kuning, α-carotenoids accumulation may not exist due to low LYCa RE. Also, higher BCH1 expression levels were observed in Ubi Kuning, suggesting a substantial zeaxanthin accumulation. Results are potential for improving carotenoid accumulation through breeding programs in cassava.